Mass Customization vs. Mass Production: Variety and Price Competition - Alptekinoğlu, Aydın; Corbett, Charles J. (Manufacturing and Service Operations Management, 2008)
We study competition between two multiproduct firms with distinct production technologies in a market where customers have heterogeneous preferences on a single taste attribute. The mass customizer (MC) has a perfectly flexible production technology and thus can offer any variety within a product space, represented by Hotelling's linear city. The mass producer (MP) has a more focused production technology and therefore offers a finite set of products in the same space. The MP can invest in more flexible technology, which reduces its cost of variety and hence allows it to offer a larger set of products; in the extreme, the MP can emulate the MC's technology and offer infinite variety. The firms simultaneously decide whether to enter the market, and the MP chooses its degree of product-mix flexibility on entry. Next, the MP designs its product line—i.e., the number and position of its products—the MC's perfectly flexible technology makes this unnecessary. Finally, both firms simultaneously set prices. We analyze the subgame-perfect Nash equilibrium in this three-stage game, allowing firm-specific fixed and variable costs that together characterize their production technology. We find that an MP facing competition from an MC offers lower product variety than an MP monopolist to reduce the intensity of price competition. We also find that the MP can survive this competition, even if it has higher fixed cost of production technology, higher marginal cost of production, or both.